Impact of political institutions on electricity generation outcomes in Sub-Saharan Africa - Ngwane, Zamangwane Beryl (My University, 2015)
Africa’s wave of democratisation since 1990 has transformed political institutions in the region. But while democracy is a desirable end in itself, considerable doubts remain about whether it is contributing to better development outcomes. This study investigates the impact of political constraints on electricity generating capacity, using cross-national data for 46 sub-Saharan African countries. It tests the hypothesis that institutions that restrain arbitrary executive authority result in higher levels of electricity generating capacity. The hypothesis is informed by the theory of credible commitment. This theory holds that political constraints provide a stable political and policy environment that reduces temptations for governments to renege on their commitments. Credible commitments are especially important in attracting investment with a long gestation period, such as investment in electricity generating capacity. In my method I use a combination of statistical analysis and nested case studies to probe the congruence of these outcomes with my hypothesis. For the nested analysis I use the statistically chosen countries of Rwanda and Kenya, which in themselves conform to the pattern of the hypothesis. My central finding is that the presence of democratic political institutions has led to improved electricity generating outcomes in African states. In this way the study contributes to the understanding of the developmental consequences of democratisation in Africa.
A Research Report Submitted to the Faculty of Humanities In partial fulfillment of the requirements for obtaining the degree of Master of Arts in International Relations
Keywords: Africa; Sub-Saharan; Politics and government; Energy policy; Democratization